Cinco espécies novas de Metharpiniinae (Amphipoda: Phoxocephalidae) no litoral do Rio de Janeiro - Bustamante, Alicelena de Oliveira (2000)
The family Phoxocephalidae comprises species inhabiting soft-bottoned surfaces. Although it is widely distributed throughout the world, such a family is poorly know on Brazilian coast. There are approximately 200 species, but only five have been registered in Ubatuha. São Paulo, BraziL namely. Microphoxus cornutus (Schellenberg, 1931): Heterophoxus videns Barnard, 1930: Pseudharpinia dentata Schellenherg, 1931: Harpiniopsis galerus Barnand, 1960 e Phoxocephalus homilis Barnard, 1960. The present study has decribed five species found along Rio de Janeiro coast. lt has included descriptions and drawings or three species from Microphoxus, one from Metharpinia and one from Grandifoxus. The last two genera have been cited for the first time in Brazil.